Investigation of some useful chemical parameters in Shea tree (Vitelaria paradoxa) nut wastewater collected after extraction of the butter: prospects of Shea butter waste valorization - E., Amofa; S. A., Abagale; O., Awo; I. , Sackey; F.K , Abagale; K.S , Twumasi (International Journal of Advanced Chemistry, 2024)
Shea butter is extracted the nut of Vitellaria paradoxa for both domestic and commercial purposes. Growing extraction and utilization of the butter especially in pharmaceutical, food and cosmetics industries result in large shea butter extraction with resultant large volumes of waste product of unknown content. Analyses of the wastewater/byproduct was carried out to review possibilities of its value addition in production of new products, or otherwise appropriate disposal. Therefore, Atomic Absorption Spectroscopy, physicochemical, and phytochemical screening methods, and extraction were used in the current study to assess antioxidant activity, BOD, calcium, iron, magnesium, lead, nickel, zinc, copper, and phytochemical content of samples of the material from Northern Ghana. The amount of residual oil was also determined. The BOD ranged from 168.00±0.00 to 86.25±6.25 mg O2/kg; Levels of magnesium in the samples ranged from 16.65 - 206.65 mg/kg, calcium from 4.72 - 19.60 mg/kg, iron was 7.75 - 14.0 mg/kg, copper from 0.02 - 0.08 mg/kg, lead from 0.33 - 1.22 mg/kg, nickel from 0.04 - 0.23 mg/kg and zinc from 3.36 - 5.80 mg/kg. Secondary metabolites present included alkaloids, phenolic, saponins, tannins and flavonoids. while residual oil extracted from the sample was between 14.67-6.46 % of the material. Mean pH was 5.95±0.05 - 6.10±0.005, and the mean temperature of the samples ranged from 24.00±0.05 to 25.25±0.05 oC at the time of analyses. From the findings the material has good and diverse content and could be used in cosmetics, pharmaceutical products or organic manure. Otherwise it should be disposed appropriately to safeguard environmental and water pollution.